A cooperative fault-tolerant control method for the coupled system based on interaction effect utilization. Issue 2 (2020) - Chang, Jing; Cieslak, Jérôme; Guo, Zongyi; Henry, David
Abstract: An active fault-tolerant control scheme is proposed in this paper for the strongly coupled MIMO systems which subject to total actuator failures. A control-oriented interaction indicator is defined in the Lyapunov stability sense and then is utilized to design the cooperative fault-tolerant control law. The proposed scheme can achieve robust tracking performance with globally uniformly ultimate boundlessness and is capable of improving transient performance (fault-tolerant ability) by wisely using the interactions. Simulation results obtained on a flight attitude control system illustrates the benefit of the proposed techniques.